In vitro and in vivo modeling systems of supratentorial ependymomas - Hatanaka, Emily A.; Breunig, Joshua J. (Frontiers in Oncology, 2024)
Ependymomas are rare brain tumors that can occur in both children and adults. Subdivided by the tumors initial location, ependymomas develop in the central nervous system in the supratentorial or infratentorial/posterior fossa region, or the spinal cord. Supratentorial ependymomas (ST-EPN) are predominantly characterized by common driver gene fusions such as ZFTA- and YAP1-fusions. Some variants of ST-EPN carry a high overall survival rate. However, high levels of inter- and intratumoral heterogeneity, limited therapeutic strategies, and tumor recurrence are among the reasons for poor patient outcomes with other ST-EPN subtypes. Modeling these molecular profiles is key in further studying tumorigenesis. Due to scarcity in patient samples, the development of pre-clinical in vitro and in vivo models that recapitulate patient tumors is imperative when testing therapeutic approaches for this rare cancer. In this review we will survey ST-EPN modeling systems, addressing the strengths and limitations, application for therapeutic targeting, and current literature findings.